BIOGENESIS OF CHLOROPLAST MEMBRANES : V. A Radioautographic Study of Membrane Growth in a Mutant of Chlamydomonas reinhardi y-1 - Goldberg, I. (The Rockefeller University Press, 1970)
The development of photosynthetic lamellae during greening of dark-grown Chlamydomonas y-1 cells was investigated by radioautography. Acetate-(3)H was used as a marker for membrane lipids. In short pulse-labeling experiments, about 50–60% of the radioactivity incorporated was found in the lipid fraction and about 25–50% in starch granules present in the chloroplast of these algae. The relative specificity of acetate-(3)H used as a marker for membranes was artificially increased through quantitative removal of the starch granules from fixed cells by amylase treatment. Analysis of turnover coefficients of different membrane constituents and of the contribution of turnover and net synthesis to the total label incorporated in pulse experiments indicated that the incorporation of acetate into specific lipids was mainly due to net synthesis. The distribution of radioactivity in the different lipid constituents at the end of a short pulse and after 30- and 60-min chases indicated that transacylation is minimal and may be disregarded as a possible cause of randomization of the label. Statistical analysis of radioautographic grain distribution and measurements of different structural parameters indicate that (a) the chloroplast volume and surface remain constant during the process, whereas the growth of the photosynthetic lamellae parallels the increase in chlorophyll; (b) the lamellae do not develop from the chloroplast envelope or from the tubular system of the pyrenoid; (c) all the lamellae grow by incorporation of new material within preexisting structures; (d) different types of lamellae grow at different rates. The pyrenoid tubular system develops faster than the thylakoids, and single thylakoids develop about twice as fast as those which are paired or fused to grana. It is concluded that growth of the membranes occurs by a mechanism of random intussusception of molecular complexes within different types of preexisting membranes.